Evaluación del proceso de modificación de almidón de papa mediante acetilación y oxidación, para su aplicación como excipiente en la industria farmacéutica a nivel laboratorio (2017)
The present project of degree has the purpose to condition the starch of potato eliminating humidity and impurities that can contain, to proceed to modify it by means of acetylation varying the volume of acetic anhydride and oxidation, varying the concentration of active chlorine of sodium hypochlorite, the modifications are Verified using infrared spectrometry and determining the degree of substituted hydroxyl groups, finally is performed the physical, chemical and pharmacotechnical characterization of the native and modified starch, in order to establish whether they correspond to a material that may become suitable for use as an excipient in the pharmaceutical.